Preparation and Characterization of Polypyrrolepolyethylene Glycol Conducting Polymer Composite Films - Lim, Mei Yee (2007)
Polypyrrole-polyethylene glycol (PPy-PEG) conducting polymer composite films were electrochemically prepared on Indium Tin Oxide (ITO) glass electrode from an aqueous solution containing pyrrole monomer, p-toluene sulfonate dopant and poly (ethylene glycol) as an insulating polymer. The PPy-PEG composite films prepared from different process conditions were characterized by Fourier Transform infrared (FT-IR) spectroscopy, electrical conductivity measurement, photoacoustic spectroscopy, X-ray diffraction (XRD) analysis and optical microscopy. The FT-IR study of PPy-PEG composite films shows the evidence of the incorporation of PEG in PPy structure forming PPy-PEG composite films. The highest electrical conductivity of 61 S/cm and thermal diffusivity of 7.88 x 10-7 m2s-1 were shown by the PPy-PEG composite film prepared from 0.20 M pyrrole, 0.10 M p-toluene sulfonate and 1 x 10-3 M PEG at 1.20 volt (vs SCE) at room temperature among all the PPy-PEG composite films produced. The conductivity data of PPy-PEG shows that with the increase in PEG concentration in the pyrrole solution, the electrical conductivity of the prepared PPy-PEG film increased up to certain level due to the increase in conjugation length and later it decreased with further increase in PEG concentration, which is again linked with the decrease in conjugation length. The measured values of thermal diffusivity and electrical conductivity for the PPy- PEG composites films showed that there was a correlation between thermal diffusivity and electrical conductivity. Both thermal diffusivity and electrical conductivity showed a similar peak for the same process condition in respective composite films. The XRD results of PPy-PEG composite films showed that the films were amorphous with very little order. The optical micrographs of PPy-PEG showed the globular surface morphology. The changes in globular surface morphology with the change in process condition of the film preparation indicated that the process parameters used to prepare the composite films had a strong influence over the surface morphology.